PENGETAHUAN DAN PERSEPSI KERENTANAN MEMENGARUHI PERILAKU SKRINING KANKER SERVIKS DENGAN METODE IVA (INSPEKSI VISUAL ASAM ASETAT) - Rachman, Machria; Faida, Nurul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Cervical cancer is one of the most prevalent types of cancer among women worldwide, adversely affecting reproductive health. However, the participation rate in cervical cancer screening using the IVA method remains significantly low. Several factors contribute to this low participation, including sociodemographic aspects (age, education level, income), knowledge, perceptions of vulnerability, and self-efficacy. The objective of this study is to identify the factors influencing cervical cancer screening using the IVA method among women of reproductive age in the Siliragung Health Center region of Banyuwangi. This research employs a quantitative method with a cross-sectional design. The population comprises 250 women of reproductive age (WUS), and a sample of 154 respondents was obtained through simple random sampling. Data were collected using a questionnaire. The results indicate that the factors significantly influencing early detection of cervical cancer are knowledge (p=0.028) and perceptions of vulnerability (p=0.000), while education level, age, income, and self-efficacy did not show a significant effect. It is imperative to provide widespread education about cervical cancer and its prevention through IVA screening among women of reproductive age.Keywords: Women of reproductive age, Early Detection of IVA, Cervical Cancer